High Efficacy Combined Microneedles Array with Methotrexate Nanocrystals for Effective Anti-Rheumatoid Arthritis - Wei F; Wang Q; Liu H; Yang X; Cao W; Zhao W; Li Y; Zheng L; Ma T; Wang Q (International Journal of Nanomedicine, 2022)
Fang Wei,1 Qiuyue Wang,1 Hang Liu,1 Xuejing Yang,1 Wenyu Cao,1 Weiman Zhao,1 Yingying Li,1 Lijie Zheng,1 Tao Ma,1,2 Qingqing Wang1– 3 1School of Pharmacy, Bengbu Medical College, Bengbu, Anhui Province, 233030, People’s Republic of China; 2Engineering Research Center for Biochemical Pharmaceuticals of Anhui Province, Bengbu Medical College, Bengbu, Anhui Province, 233030, People’s Republic of China; 3Bengbu BBCA Medical Science Co., Ltd., Bengbu, Anhui Province, 233030, People’s Republic of ChinaCorrespondence: Qingqing Wang; Tao Ma, School of Pharmacy, Bengbu Medical College, Bengbu, Anhui Province, 233030, People’s Republic of China, Tel +86 15605528300 ; +86 13855266592, Email qingqingwang@bbmc.edu.cn; matao1992@foxmail.comIntroduction: Methotrexate (MTX) is the first-line drug for the treatment of rheumatoid arthritis (RA) in several countries. However, MTX has an extremely low solubility in water, and the side effects caused by its delivery mode restrict its curative effect. In this study, we designed a dissolving microneedles array (DMNA) containing MTX nanocrystals (MTX-NCs) (MTX-NC@DMNA) to improve the treatment of RA. DMNA-based drug delivery combines the advantages of patient compliance with the use of transdermal drug delivery systems and high-efficiency injection administration; thus, it can mitigate the side effects that result from current administration routes. Carrier-free and surfactant-free MTX-NCs were prepared to overcome bioavailability limitations and poor drug loading problems.Methods: The MTX-NCs prepared by reverse solvent precipitation method was encapsulated in the DMNA. The morphology, mechanical properties, safety, stability and in vivo dissolution were evaluated, and its pharmacodynamic characteristics were assessed in a rat model of RA.Results: The particle size of the MTX-NCs was 148.1 ± 10.1 nm. The MTX-NC@DMNA were found to be rigid enough to penetrate the skin and deliver the drug successfully. The results indicated effective skin recovery after removal of the DMNA. It was found that the MTX-NC@DMNA significantly reduced foot swelling in the rats and regulated the balance in the levels of related cytokines. It also reduced pathological damage to the synovium, joint, and cartilage, and effectively alleviated organ injury in the rats.Conclusion: Transdermal administration of MTX-NC@DMNA may be an effective approach for treating RA.Graphical Abstract: Keywords: nanocrystals, inflammation, dissolving microneedles array, transdermal, rheumatoid arthritis